PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI KONSUMEN ES KRIM DI TOKO MOMOYO DRIYOREJO KECAMATAN GRESIK - Leonita; Sofyan; Cucu Hayati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This study aims to examine the influence of the marketing mix, consisting of product, price, promotion, and place, on consumer purchase interest at Momoyo Store, Driyorejo District, Gresik. This research employs a quantitative approach with an associative design. Data were collected through questionnaires distributed to 86 respondents selected as research samples. The research instrument used a Likert scale that had been tested for validity and reliability. Data analysis included validity testing, reliability testing, classical assumption tests (normality, multicollinearity, and heteroscedasticity), t-test (partial), F-test (simultaneous), multiple linear regression analysis, and the coefficient of determination (R²) using SPSS version 23. The results revealed that product, price, and promotion variables did not significantly affect consumer purchase interest, while the place variable had a significant effect. Furthermore, the F-test results indicated that product, price, promotion, and place variables jointly had a significant influence on consumer purchase interest. The coefficient of determination (R²) value of 51.5% shows that promotion and store location are the main factors influencing consumer purchase interest at Momoyo Store Driyorejo, while the remaining 48.5% is influenced by other factors outside this study